PENGARUH HARGA JUAL, PROMOSI DAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PP. SETIA KAWAN DI PURWOKERTO - Pikir Wisnu Wijayanto (Pro Bisnis, 2009)
The purposes of this research area to know the influence of selling price has the most influence to the selling volume in Setia Kawan Plastic Company Purwokerto. The research method that is used is study case with double linier regression analysis tools and elasticity coefficient. For testing the first hypothesis that said the price selling, promotion, and distribution have the meaning influence to selling volume is used double linear price has the most influence to selling volume is compared with promotion and distribution, is used elasticity analysis. Based on the research’s result and data analysis, it can be concluded that selling price variable, promotion, and distribution have the meaning influence to selling volume in Setia Kawan Plastic Company Purwokerto.